THE IMPACT OF SCHOOL LITERACY MOVEMENT (GSL) ON THE LITERACY ABILITY OF THE FIFTH GRADERS AT SD NEGERI GUNUNG SARI, RAPPOCINI DISTRICT, MAKASSAR CITY - Syawaluddin, Ahmad; haedah, Nur (Universitas Pendidikan Ganesha, 2017)
This research was aimed at knowing the impact of (GLS) on the students’ literacy ability of the fifth graders at SD Negeri Gunung Sari I, Rappocini district, Makassar city in the school year 2016/2017. The research approach used a quantitative approach with Pre-experimental Research design. The sample was selected with purposive sampling by choosing class V as experiment class with the total number of 66 students and those who were present were 50 students. The techniques of data collection used in this research were test and documentation. The data collected from the literacy ability test result were then analyzed using descriptive statistical analysis and inferential statistical analysis using sample t-test of Wilcoxon Test by using the test of two sides (two tailed test). To test the normality of the data distribution, Kolmogrov-Smirnov Normality Test was used with Asymp Sig. (2-Tailed) of 0.002 for pretest data and 0.003 for posttest data. Literacy ability on initial test (pretest) was in very satisfactory category with the mean of 83.99 and the literacy ability in the final test (posttest) was in very satisfactory category with the mean of 90.23. Hypothesis testing was done by using Wilcoxon Test Asymp Sig. (2-tailed) the value was 0.00 < 0.05. The conclusion of research based on the result of analysis showed that there is an impact of school literacy movement (GLS) on students’ literacy ability of fifth graders of SD Negeri Gunung Sari I in Rappocini disctrict, Makassar city